Protective role of salicylic acid applied before cold stress on antioxidative system and protein patterns in barley apoplast - Mutlu, S.; Karadagoglu, O.; Atici, O.; Nalbantoglu, B. (ACAD SCIENCES CZECH REPUBLIC, INST EXPERIMENTAL BOTANY, 2013)
This study was carried out to better understand the role of salicylic acid (SA) applied before cold stress in the cold tolerance mechanism. Two barley (Hordeum vulgare) cultivars, cold-sensitive (Akhisar) and cold-tolerant (Tokak), were used and 0.1 mM SA was applied to 7-d-old barley seedlings growing under control conditions (20/18 A degrees C). The seedlings were transferred to cold chamber (7/5 A degrees C) at the age 14, 21, and 28 d. After three days, the leaves were harvested to determine the activities of apoplastic antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POX) and ice nucleation activity and electrophoretic patterns of apoplastic proteins. Cold treatment decreased the activities of all enzymes in cold-sensitive cultivar, however, it increased CAT and POX activities in cold-tolerant cultivar. Exogenous SA increased enzyme activities in both cultivars. Ice nucleation activity increased by cold treatment, especially in 17-d-old seedlings in both cultivars. In addition, SA treatment increased ice nucleation activity in all examined samplings in both cultivars. SA treatment caused accumulation or de novo synthesis of some apoplastic proteins. The results of the present study show that exogenous SA can improve cold tolerance by regulating the activities of apoplastic antioxidative enzymes, ice nucleation activity, and the patterns of apoplastic proteins.
Keywords: catalase; cold tolerance; Hordeum vulgare; ice nucleation activity; peroxidase; superoxide dismutase; ANTIFREEZE PROTEINS; FREEZING TOLERANCE; CHILLING TOLERANCE; LIPID-PEROXIDATION; HYDROGEN-PEROXIDE; LOW-TEMPERATURE; SALT-TOLERANT; ENZYMES; LEAVES; WHEAT; Plant Sciences